Pengaruh Progressive Muscle Relaxation (PMR) Terhadap Intensitas Nyeri Pasien Pasca Operasi Seksio Sesarea Hari Pertama - Ni Wayan Noviani, Fitria, Ni Made Darmiyanti, (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2026)
This study aimed to evaluate the effectiveness of Progressive Muscle Relaxation (PMR) on pain intensity in post-cesarean section patients on the first postoperative day. Method A quasi-experimental design with a non-randomized control design was conducted at the General Hospital of Negara Regency, Bali Province, from March to May 2025. A total of 60 post-cesarean section patients were recruited using purposive sampling and allocated into two groups: the intervention group (n=30) received a single 20-minute session of PMR, while the control group (n=30) received standard care. Pain intensity was measured using the Visual Analog Scale (VAS) before and after the intervention. Data were analyzed using paired and independent t-tests. The intervention group demonstrated a significant reduction in pain intensity, with mean VAS scores decreasing from 6.8 ± 1.1 to 3.9 ± 1.0 (mean difference = 2.9; p<0.001; Cohen’s d = 2.6). In contrast, the control group showed no significant change (6.7 ± 1.2 to 6.1 ± 1.0; mean difference = 0.6; p=0.064). The between-group difference was statistically significant (p<0.001). PMR is effective in reducing pain intensity in post-cesarean section patients on the first postoperative day. This non-pharmacological technique can be integrated into standard postpartum care as a safe, low-cost intervention to enhance maternal comfort and reduce reliance on analgesics